Comparative Diagnostic Accuracy of Digital and Conventional Radiography in the Detection of Bone Fractures - es Mahwish Zahra, Ifrah Ata Hashmi, Hafiz Muhammad Amir Jamil, Nooshin Akhtar, Hira Bushra, Rafia Irum, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Bone fractures represent a substantial proportion of cases presenting to emergency and orthopedic departments worldwide, including in resource-limited settings like Nishtar medical university/Hospital, Multan. Timely and precise diagnosis is vital for the initiation of appropriate treatment, minimizing complications, and improving long-term functional outcomes. Conventional radiography (X-ray) has historically been the cornerstone of fracture detection. However, recent advancements in digital imaging technology have introduced digital radiography as a potentially superior alternative, offering improved image resolution, faster processing times, ease of storage and retrieval, and reduced radiation exposure. Despite these advantages, its diagnostic performance in comparison to conventional methods remains a subject of investigation, particularly in developing healthcare settings. Objective: This study aimed to compare the diagnostic accuracy of digital and conventional radiography in the detection of bone fractures among patients presenting to the emergency and orthopedic departments at Nishtar medical university/Hospital, Multan. Methodology: A descriptive cross-sectional study was carried out over an eight-month period from 1st October 2022 to 31st March 2023. A total of 200 patients of various age groups and both genders, presenting with clinical suspicion of bone fractures, were enrolled through consecutive sampling. Each patient underwent both conventional and digital radiographic imaging of the affected area. The radiographs were independently interpreted by two qualified radiologists who were blinded to each other’s findings and to the clinical details. The findings were then validated against a reference standard, which included either computed tomography (CT) findings or intraoperative surgical confirmation. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic concordance rates were calculated and compared for both modalities. Results: The study revealed that digital radiography outperformed conventional radiography in terms of both sensitivity and specificity. Digital radiography demonstrated a sensitivity of 94.5% and a specificity of 91.2%, whereas conventional radiography showed a sensitivity of 83.0% and a specificity of 85.0%. The difference in diagnostic performance was particularly evident in the detection of fractures involving smaller or more complex anatomical regions, such as the wrist, hand, ankle, and foot. Inter-observer agreement was also higher for digital images, suggesting better clarity and interpretability. Moreover, the turnaround time for digital imaging was shorter, facilitating faster decision-making in emergency settings. Conclusion: The findings of this study indicate that digital radiography provides significantly higher diagnostic accuracy compared to conventional X-ray, particularly in identifying subtle or small bone fractures. Given its superior image quality, reduced radiation dose, and operational efficiency, digital radiography should be considered the preferred imaging modality in emergency and orthopedic practice, especially in facilities where resources permit. The integration of digital systems may lead to improved diagnostic confidence, faster clinical decision-making, and ultimately, better patient outcomes. Keywords: Digital radiography, conventional X-ray, bone fractures, diagnostic accuracy, emergency imaging, orthopedic trauma, sensitivity, specificity